2001
DOI: 10.1046/j.1365-294x.2001.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical genetic structure of the introduced wasp Vespula germanica in Australia

Abstract: The wasp Vespula germanica is a highly successful invasive pest. This study examined the population genetic structure of V. germanica in its introduced range in Australia. We sampled 1320 workers and 376 males from 141 nests obtained from three widely separated geographical areas on the Australian mainland and one on the island of Tasmania. The genotypes of all wasps were assayed at three polymorphic DNA microsatellite markers. Our analyses uncovered significant allelic differentiation among all four V. german… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 48 publications
6
44
1
1
Order By: Relevance
“…(2014a) showed that workers from native colonies of V. pensylvanica were always produced by a single queen, whereas colonies in the invasive range often contained workers produced by multiple queens (Goodisman et al. 2001; Hanna et al. 2014a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2014a) showed that workers from native colonies of V. pensylvanica were always produced by a single queen, whereas colonies in the invasive range often contained workers produced by multiple queens (Goodisman et al. 2001; Hanna et al. 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…A similar, significant isolation‐by‐distance relationship, spanning approximately 225 km, was found for V. germanica in its invasive region of Australia (Goodisman et al. 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty microliters of 5% Chelex solution was added to the egg samples; the tubes were vigorously vortexed and centrifuged for 5 min. DNA was extracted from adults following the methods of Goodisman et al (2001).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, this effect could influence the genetic components within populations. In annual eusocial wasps, apparent IBD and/or population structuring have rarely been observed (Queller et al 1992;Strassmann et al 1995;Hoffman et al 2008), with a few exceptions (Davis et al 1990;Goodisman et al 2001). Together, these studies suggest that eusocial wasps could be strong fliers; this trait together with an annual life history could impede population structuring and/or mask patterns of IBD within populations.…”
Section: Introductionmentioning
confidence: 99%